Sargassum horneri (Turner) C. Agardh ethanol extract inhibits the fine dust inflammation response via activating Nrf2/HO-1 signaling in RAW 264.7 cells - Thilina U. Jayawardena; K. K. Asanka Sanjeewa; I. P. Shanura Fernando; Bo Mi Ryu; Min-Cheol Kang; Youngheun Jee; Won Woo Lee; You-Jin Jeon (BMC, 2018)
Abstract Background Among the different kinds of pollution, air pollution continues to increase globally. East Asia is considered to be significantly affected. As a result, the populations in these regions face serious health issues including respiratory disorders. This study investigated the impact of fine dust (FD) particles (CRM No. 28) on macrophage cells as a model for alveolar lung cells. Methods The research focused on inflammation and oxidative stress induced by FD and Sargassum horneri (Turner) C. Agardh ethanol extract (SHE) as a potential treatment. S. horneri is a type of brown algae that has demonstrated anti-inflammatory effects against RAW 264.7 macrophages in previous studies. MTT, Griess, ELISA, western blotting, and mRNA expression analyses using PCR techniques were used in this study. Results The optimum FD concentration was determined to be 125 μg mL− 1. FD particles stimulated inflammatory mediators production (iNOS, COX-2, and PGE2) and pro-inflammatory cytokines (IL-1β, IL-6, and TNF-α), leading to NO production. These mediators were dose-dependently downregulated by treatment with SHE. IL-6 and TNF-α were identified as biomarkers for FD. SHE treatment induced HO-1 and Nrf2 activity in a dose-dependent manner under FD stimulation. This confirmed the cytoprotective effect against oxidative stress induced via FD. Furthermore, treatment of the cells with a p38 MAPK inhibitor (SB202190) induced FD-stimulated NO production. Conclusions The results suggest that SHE increases macrophage cellular resistance to FD-induced inflammation and oxidative stress, probably via the p38 MAPK pathway and Nrf2/HO-1 expression.